Embedded systems design - Heath, Steve, ....- (Oxford : Newnes, 2003)
Samenvatting:In this new edition the latest ARM processors and other hardwaredevelopments are fully covered along with new sections on Embedded Linuxand the new freeware operating system eCOS. The hot topic of embeddedsystems and the internet is also introduced. In addition a fascinatingnew case study explores how embedded systems can be developed andexperimented with using nothing more than a standard PC.
Keywords: Embedded computer systems -- Design and construction; Formele methoden; Programmatuurontwikkeling; Real-time computersystemen